Performance Evaluation of Unicast Reactive Ad-hoc Routing Protocols for Underwater Wireless Sensor Networks - Gunagi, Suhasini S; SA, Rajashekar (International Journal of Computer Sciences and Engineering, 2025)
UWC (Under Water Communications) will enable many safety, military, Environmental and scientific applications. Instruments can be remotely controlled in ocean observatories using wireless signal transmission which is crucial and coordination of autonomous underwater vehicles and robots will be enabled, which plays the role of mobile nodes in future ocean observation networks with their re-configurability and flexibility. Underwater applications can be made viable with efficient communication protocols among underwater devices which are based on acoustic wireless technology with distance over one hundred meters will be enabled to make underwater applications viable because of its high attenuation and scattering which will affect radio and optical waves. New efficient and reliable communication protocols are required to network multiple devices which are mobile or static over the multiple hops which are required for the unique characteristics of an underwater acoustic channel, such as time varying multipath, fading, distance and limited dependent bandwidth and high propagation delays. For packet transmission, MANETs use varieties of routing protocols which are classified as pro-active, re-active and hybrid routing protocols. In this paper, two on-demand unicast reactive routing protocols are considered namely Ad-hoc On Demand Distance Vector (AODV) and Dynamic Source Routing (DSR) in order to evaluate their performance based on Quality of Service (QoS) for UWSN. Both AODV and DSR routing protocols are implemented on the basis of on-demand gateway discovery algorithm where each node can communicate with each other through the entry and exit point of a network as and when required. Through simulation with increasing the node density using ns2 network simulator, we perceive that the performance parameters of AODV and DSR routing protocols are analysed